Evaluasi Pelaksanaan Standar Operasional Prosedur Pengelolaan Program Ketahanan Pangan Berbasis Alokasi Dana Desa di Desa Teluk Rimba, Kec. Koto Gasib, Kabupaten Siak - Novrida Talis; Amrizal Amrizal; Iwan Setiadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to evaluate the implementation of Standard Operating Procedures (SOPs) in the management of the Village Fund Allocation (ADD)-based food security program in Teluk Rimba Village, Koto Gasib District, Siak Regency. The method used in this study was a qualitative approach through interviews, observation, and documentation with village officials, village facilitators, and beneficiaries. The results indicate that although the SOPs were developed through village deliberations and serve as guidelines for program planning, implementation, and reporting, their implementation still faces various obstacles such as limited community understanding, delays in distribution, and weak oversight. In general, the SOPs have been implemented according to regulations, but improvements in socialization, coordination, and monitoring are needed to optimize the effectiveness, accountability, and sustainability of the food security program.